Mechanoluminescent material and its preparation method and application
By doping Bi3+ in Ca5Ga4.8Al1.2O14:Sm3+ material to form Ca5Ga4.8Al1.2O14:Bi3+, Sm3+ materials, the problem of pre-irradiation charging of existing electroluminescent materials is solved, and high luminescence intensity, long-term force electroluminescence and good stability are achieved. It is suitable for applications such as multi-color anti-counterfeiting labels.
Patent Information
- Application Number
- CN202411718728.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-11-28
AI Technical Summary
Existing powerful electroluminescent materials have low luminescence intensity, low sensitivity and poor stability, and require pre-irradiation charging to produce electroluminescence, which seriously hinders its development and application.
Ca5Ga4.8Al1.2O14:D material, where D includes Bi3+ and Sm3+, and is doped with Bi3+ without pre-irradiation to increase the trap concentration and depth of the material so that it can be charged under natural light and generates force-emission.
It achieves high force electroluminescence intensity, high sensitivity and good stability without pre-irradiation, and has a long time to luminescence, making it suitable for applications such as multi-color anti-counterfeiting labels.
Smart Images

Figure CN119193151B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid luminescent materials, and in particular relates to a mechanoluminescent material and a preparation method and application thereof. Background Art
[0002] Compared with traditional powder materials, photoluminescent materials, electroluminescent materials or mechanoluminescent materials are widely studied as green and smart materials. However, the current mechanoluminescent materials have low luminescence intensity, low sensitivity and poor stability. They need to be irradiated with ultraviolet rays or X-rays in advance for charging to produce mechanoluminescence, which seriously hinders the development and application of mechanoluminescent materials. Summary of the invention
[0003] In view of this, the purpose of the present invention is to provide a mechanoluminescent material and a preparation method and application thereof. The mechanoluminescent material of the present invention does not require pre-irradiation, has high mechanoluminescent intensity and high sensitivity, and has a long mechanoluminescent time and good stability without charging conditions.
[0004] The present invention provides a mechanoluminescent material, the chemical formula of which is Ca5Ga 4.8 Al 1.2 O 14 :D, wherein D includes Bi 3+ and Sm 3+ .
[0005] Preferably, the D also includes Tb 3+ .
[0006] Preferably, the Bi 3+ 、Sm 3+ and Tb 3+ The molar ratio of substances is (0.002~0.008):(0.02~0.12):(0.02~0.12).
[0007] The present invention also provides a method for preparing the mechanoluminescent material described in the above technical solution, comprising the following steps:
[0008] H3BO3, Al2O3, CaO, Ga2O3, Bi2O3 and Sm2O3 are mixed and calcined to obtain the mechanoluminescent material.
[0009] Preferably, the calcination temperature is 1170-1270° C., and the holding time is 3.5-5.5 hours.
[0010] Preferably, the molar ratio of H3BO3, Al2O3, CaO, Ga2O3, Bi2O3 and Sm2O3 is (0.001~0.003): 0.6: (4.5~5.5): 2.4: (0.001~0.004): (0.01~0.06).
[0011] Preferably, Tb4O7 is added to the mixture of H3BO3, Al2O3, CaO, Ga2O3, Bi2O3 and Sm2O3.
[0012] Preferably, the molar ratio of H3BO3, Al2O3, CaO, Ga2O3, Bi2O3, Sm2O3 and Tb4O7 is (0.001~0.003): 0.6: (4.5~5.5): 2.4: (0.001~0.004): (0.01~0.06): (0.01~0.06).
[0013] The present invention also provides the use of the mechanoluminescent material described in the above technical solution or the mechanoluminescent material obtained by the above preparation method in an anti-counterfeiting label.
[0014] The present invention also provides a mechanoluminescent composite material, comprising the following raw materials in parts by weight:
[0015] 3.5~4.5 parts of mechanoluminescent material, 2.5~3.5 parts of molding agent and 0.8~1.2 parts of curing agent;
[0016] The mechanoluminescent material is the mechanoluminescent material described in the above technical solution or the mechanoluminescent material obtained by the above preparation method.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] The present invention provides a mechanoluminescent material, the chemical formula of which is Ca5Ga 4.8 Al 1.2 O 14 :D, wherein D includes Bi 3+ and Sm 3+ The present invention will Bi 3+ Doped in Ca5Ga 4.8 Al 1.2 O 14 :Sm 3+ In the material, a small amount of Bi is doped 3+ That is, the obtained mechanoluminescent material has abundant traps, and the high trap concentration and deep traps enable the material to be charged under natural light, store electrons, and generate mechanoluminescence. The mechanoluminescent material of the present invention does not require pre-irradiation, has high mechanoluminescence intensity and high sensitivity, and has a long mechanoluminescence time and good stability under non-charging conditions.
[0019] The selection of rare earth ions in the mechanoluminescent matrix is very demanding, so how to achieve the luminescence of different rare earth ions in a single matrix is an important research topic. The yellow light mechanoluminescent material of the present invention has a chemical formula of Ca5Ga 4.8 Al 1.2 O 14 :Bi 3+ ,Sm 3+ ,Tb 3+ . The matrix of the present invention has a very obvious mechanoluminescence effect, can realize self-supply mechanoluminescence, and can also realize more than two kinds of red and yellow adjustable mechanoluminescence at the same time. The present invention successfully realizes mechanoluminescence from red to yellow in a matrix, realizes color adjustment, broadens the application scenarios of mechanoluminescent materials, and has better encryption performance for multi-color luminescent materials in the field of anti-counterfeiting.
[0020] The present invention provides a red or yellow mechanoluminescent material that does not require charging. The material can be directly rubbed in the dark, or subjected to tensile stress and compressive stress tests after being prepared into a composite material, and can show obvious mechanoluminescence. This material can produce mechanoluminescence under various forms of force, and shows good environmental adaptability, and has great application potential. Since the material can achieve red and yellow mechanoluminescence, it has great potential in multi-color anti-counterfeiting labels. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 The XRD diffraction patterns of the mechanoluminescent materials of Examples 1 and 2;
[0023] Figure 2 This is a scanning electron microscope image (SEM) of the material of Example 1;
[0024] Figure 3 The spectra of the mechanoluminescent materials of Examples 1, 3 to 5 and the mechanoluminescent materials of Examples 2, 6 to 8;
[0025] Figure 4 The spectra of the mechanoluminescent materials of Examples 1 and 2;
[0026] Figure 5 This is a 15-day continuous electroluminescence test effect diagram of the materials of Example 1 to Example 2;
[0027] Figure 6 This is a schematic diagram of the application example 1 of the electroluminescent composite material in an anti-counterfeiting label. DETAILED DESCRIPTION
[0028] The present invention provides a mechanoluminescent material, the chemical formula of which is Ca5Ga 4.8 Al 1.2 O 14 :D, wherein D includes Bi 3+ and Sm 3+ .
[0029] In the present invention, unless otherwise specified, the materials and equipment used are commercially available products in the art.
[0030] The mechanoluminescent material of the present invention comprises Bi 3+ Doped Ca5Ga 4.8 Al 1.2 O 14 :Sm 3+ Materials, by Bi 3+ The introduction of ions promotes the formation of deep traps in the material, allowing the material to produce mesoluminescence without the need for pre-irradiation charging. Furthermore, the appropriate amount of aluminum oxide in the material improves the luminescence intensity and stability of the material.
[0031] In the present invention, the Bi 3+ and Sm 3+ The molar ratio of is preferably (0.002-0.008): (0.02-0.12), more preferably 1:10. 3+ and Sm 3+ When the mechanoluminescent material (Ca5Ga 4.8 Al 1.2 O 14 : Bi 3+ , Sm 3+ ) is a red light luminescent material. The chemical formula of the luminescent material is preferably Ca5Ga 4.8 Al 1.2 O 14 : 0.006Bi 3+ , 0.06Sm 3+ .
[0032] In the present invention, the D preferably also includes Tb 3+ , mechanoluminescent materials (Ca5Ga 4.8 Al 1.2 O 14 : Bi 3+ , Sm 3+ ,Tb 3+ ) is a yellow photoluminescent material.
[0033] In the present invention, the Bi 3+ 、Sm 3+ and Tb 3+ The molar ratio of Tb is preferably (0.002-0.008): (0.02-0.12): (0.02-0.12), and more preferably 1: 10: 10. 3+ , achieving the transition from red light to yellow light. The chemical formula of the mechanoluminescent material is preferably Ca5Ga 4.8 Al 1.2 O 14 :0.006Bi 3+ ,0.06Sm 3+ ,0.06Tb 3+ .
[0034] The present invention also provides a method for preparing the mechanoluminescent material described in the above technical solution, comprising the following steps:
[0035] H3BO3, Al2O3, CaO, Ga2O3, Bi2O3 and Sm2O3 are mixed and calcined to obtain the mechanoluminescent material.
[0036] In the present invention, the molar ratio of H3BO3 to CaO is preferably (0.001-0.003): (4.5-5.5), specifically 0.002: 5 or 0.001: 4.5. The H3BO3 is a co-solvent, which can reduce the calcination (sintering) temperature.
[0037] In the present invention, the molar ratio of Al2O3 to Ga2O3 is preferably (0.4-0.8):2.4, specifically 0.6:2.4. The Al2O3 can improve the luminous intensity and stability of the material.
[0038] In the present invention, the molar ratio of CaO to Ga2O3 is preferably (4.5-5.5): 2.4, specifically 5: 2.4 or 4.5: 2.4. The CaO and Ga2O3 are the main matrix for preparing the mechanoluminescent material.
[0039] In the present invention, the molar ratio of Sm2O3 to CaO is preferably (0.01-0.06): (4.5-5.5), more preferably (0.02-0.04): (4.5-5.5), and specifically can be 0.03: 5 or 0.03: 4.5. 3+ It is the luminescent center of red photoluminescent material.
[0040] In the present invention, the molar ratio of H3BO3, Al2O3, CaO, Ga2O3, Bi2O3 and Sm2O3 is preferably (0.001~0.003): 0.6: (4.5~5.5): 2.4: (0.001~0.004): (0.01~0.06), specifically 0.002: 0.6:5: 2.4: 0.003: 0.03 or 0.012: 0.6: 5.3: 2.4: 0.004: 0.04.
[0041] In the present invention, the calcination preferably further comprises mixing and grinding H3BO3, Al2O3, CaO, Ga2O3, Bi2O3 and Sm2O3, and the grinding is preferably carried out in an agate mortar; the particle size of the powder after the grinding is preferably not more than 0.075 mm (through a 200 mesh sieve).
[0042] In the present invention, the calcination temperature is preferably 1170-1270°C, more preferably 1170-1240°C, specifically 1200°C, and the holding time is preferably 3.5-5.5 hours, specifically 4 hours. The heating rate from room temperature to the calcination temperature is preferably 6-8°C / min. The present invention preferably places H3BO3, Al2O3, CaO, Ga2O3, Bi2O3 and Sm2O3 powders in an alumina crucible and performs the calcination in a box furnace. During the calcination process, the synthesized Ca5Ga 4.8 Al 1.2 O 14 :Bi 3+ ,Sm 3+ The calcination preferably includes cooling, and the cooling is preferably carried out along with the furnace.
[0043] In the present invention, the mixture of H3BO3, Al2O3, CaO, Ga2O3, Bi2O3 and Sm2O3 is preferably mixed with Tb4O7.
[0044] In the present invention, the molar ratio of H3BO3, Al2O3, CaO, Ga2O3, Bi2O3, Sm2O3 and Tb4O7 is preferably (0.001-0.003): 0.6: (4.5-5.5): 2.4: (0.001-0.004): (0.01-0.06): (0.01-0.06), and specifically can be 0.002: 0.6: 5: 2.4: 0.003: 0.03: 0.03 or 0.001: 0.5: 5: 2.5: 0.0025: 0.03: 0.03. The addition amount of Bi2O3 described in the present invention has a good mechanoluminescence effect, and the mechanoluminescence can be sustained for 15 days under the condition of no charging.
[0045] The present invention also provides the use of the mechanoluminescent material described in the above technical solution or the mechanoluminescent material obtained by the above technical preparation method in anti-counterfeiting labels.
[0046] The present invention also provides a mechanoluminescent composite material, comprising the following raw materials in parts by weight:
[0047] 3.5~4.5 parts of mechanoluminescent material, 2.5~3.5 parts of molding agent and 0.8~1.2 parts of curing agent;
[0048] The mechanoluminescent material is the mechanoluminescent material described in the above technical solution or the mechanoluminescent material obtained by the above preparation method.
[0049] In the present invention, the molding agent preferably includes epoxy resin and / or polydimethylsiloxane (PDMS), more preferably epoxy resin, and the epoxy resin is preferably epoxy resin A glue. The molding agent molds the mesoluminescent powder material.
[0050] In the present invention, the curing agent preferably includes epoxy resin B. The curing agent promotes the molding of the material.
[0051] In the present invention, the mechanoluminescent composite material preferably comprises the following raw materials in parts by mass: 4 parts of mechanoluminescent material, 3 parts of molding agent and 1 part of curing agent.
[0052] The present invention also provides a method for preparing the mechanoluminescent composite material described in the above technical solution, comprising the following steps:
[0053] The mechanoluminescent material, the molding agent and the curing agent are mixed and cured to obtain the mechanoluminescent composite material.
[0054] In the present invention, the curing temperature is preferably 65-75°C, specifically 70°C, and the curing time is preferably 50-70 minutes, specifically 50 minutes or 60 minutes. In the present invention, the mesoluminescent material, the molding agent and the curing agent are preferably placed in a polytetrafluoroethylene mold and heated in an oven for curing.
[0055] The present invention applies the composite material to the field of anti-counterfeiting to prepare an anti-counterfeiting coating. When the anti-counterfeiting coating is uncovered, mechanoluminescence is generated due to the force applied to the material.
[0056] In order to further illustrate the present invention, the following describes in detail the mechanoluminescent material provided by the present invention and its preparation method and application in combination with the accompanying drawings and embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0057] Embodiment 1
[0058] A method for preparing a yellow light-induced luminescent material comprises the following steps:
[0059] The raw materials H3BO3, Al2O3, CaO, Ga2O3, Bi2O3, Sm2O3 and Tb4O7 were placed in an agate mortar at a molar ratio of 0.002: 0.6: 5:2.4: 0.003: 0.03: 0.03 and ground for 30 minutes to mix evenly. Then, they were put into an alumina crucible, covered and placed in a box furnace and sintered at 1200°C for 4 hours. Then, the temperature was lowered along with the furnace to obtain a yellow photoluminescent material.
[0060] The yellow photoluminescent material obtained in Example 1 has a chemical formula of Ca5Ga 4.8 Al 1.2 O 14 : 0.006Bi 3+ ,0.06Sm 3+ ,0.06Tb 3+ .
[0061] Embodiment 2
[0062] A method for preparing a red photoluminescent material comprises the following steps:
[0063] The raw materials H3BO3, Al2O3, CaO, Ga2O3, Bi2O3 and Sm2O3 were placed in an agate mortar at a molar ratio of 0.002: 0.6: 5: 2.4: 0.003: 0.03, ground for 30 minutes and mixed evenly, then put into an alumina crucible, covered and placed in a box furnace and sintered at 1200°C for 4 hours, and then cooled with the furnace to obtain a red photoluminescent material.
[0064] The red photoluminescent material obtained in Example 2 has a chemical formula of Ca5Ga 4.8 Al 1.2 O 14 : 0.006Bi 3+ ,0.06Sm 3+ .
[0065] Embodiment 3
[0066] The raw materials H3BO3, Al2O3, CaO, Ga2O3, Bi2O3, Sm2O3 and Tb4O7 were placed in an agate mortar at a molar ratio of 0.002: 0.6: 5:2.4: 0.001: 0.03: 0.03, ground for 30 minutes and mixed evenly, then put into an alumina crucible, covered and placed in a box furnace and sintered at 1200°C for 4 hours, and then cooled with the furnace to obtain a yellow photoluminescent material.
[0067] The yellow photoluminescent material obtained has the chemical formula of Ca5Ga 4.8 Al 1.2 O14 :0.002Bi 3+ ,0.06Sm 3+ ,0.06Tb 3+ .
[0068] Embodiment 4
[0069] The raw materials H3BO3, Al2O3, CaO, Ga2O3, Bi2O3, Sm2O3 and Tb4O7 were placed in an agate mortar at a molar ratio of 0.002: 0.6: 5:2.4: 0.002: 0.03: 0.03, ground for 30 minutes and mixed evenly, then put into an alumina crucible, covered and placed in a box furnace and sintered at 1200°C for 4 hours, and then cooled with the furnace to obtain a yellow photoluminescent material.
[0070] The yellow photoluminescent material obtained has the chemical formula of Ca5Ga 4.8 Al 1.2 O 14 :0.004Bi 3+ ,0.06Sm 3+ ,0.06Tb 3+ .
[0071] Embodiment 5
[0072] The raw materials H3BO3, Al2O3, CaO, Ga2O3, Bi2O3, Sm2O3 and Tb4O7 were placed in an agate mortar at a molar ratio of 0.002: 0.6: 5:2.4: 0.004: 0.03: 0.03, ground for 30 minutes and mixed evenly, then put into an alumina crucible, covered and placed in a box furnace and sintered at 1200°C for 4 hours, and then cooled with the furnace to obtain a yellow photoluminescent material.
[0073] The yellow photoluminescent material obtained has the chemical formula of Ca5Ga 4.8 Al 1.2 O 14 : 0.008Bi 3+ , 0.06Sm 3+ ,0.06Tb 3+ .
[0074] Embodiment 6
[0075] The raw materials H3BO3, Al2O3, CaO, Ga2O3, Bi2O3 and Sm2O3 were placed in an agate mortar at a molar ratio of 0.002: 0.6: 5: 2.4: 0.001: 0.03, ground for 30 minutes and mixed evenly, then put into an alumina crucible, covered and placed in a box furnace and sintered at 1200°C for 4 hours, and then cooled with the furnace to obtain a red photoluminescent material.
[0076] The obtained red photoluminescent material has the chemical formula of Ca5Ga 4.8 Al 1.2 O 14 :0.002Bi 3+ ,0.06Sm 3+ .
[0077] Embodiment 7
[0078] The raw materials H3BO3, Al2O3, CaO, Ga2O3, Bi2O3 and Sm2O3 were placed in an agate mortar at a molar ratio of 0.002: 0.6: 5: 2.4: 0.002: 0.03, ground for 30 minutes and mixed evenly, then put into an alumina crucible, covered and placed in a box furnace and sintered at 1200°C for 4 hours, and then cooled with the furnace to obtain a red photoluminescent material.
[0079] The obtained red photoluminescent material has the chemical formula of Ca5Ga 4.8 Al 1.2 O 14 :0.004Bi 3+ ,0.06Sm 3+ .
[0080] Embodiment 8
[0081] The raw materials H3BO3, Al2O3, CaO, Ga2O3, Bi2O3 and Sm2O3 were placed in an agate mortar at a molar ratio of 0.002: 0.6: 5: 2.4: 0.004: 0.03, ground for 30 minutes and mixed evenly, then put into an alumina crucible, covered and placed in a box furnace and sintered at 1200°C for 4 hours, and then cooled with the furnace to obtain a red photoluminescent material.
[0082] The obtained red photoluminescent material has the chemical formula of Ca5Ga 4.8 Al 1.2 O 14 :0.008Bi 3+ ,0.06Sm 3+ .
[0083] Performance Characterization
[0084] Figure 1 The XRD diffraction patterns of the luminescent materials of Example 1 and Example 2 are shown in Table 1. 4.8 Al 1.2 O 14 The standard diffraction peaks are matched by doping with Bi 3+ , and then co-doped with Sm 3+ , Tb 3+ Ion or single doping Sm 3+The crystal structure will not be changed.
[0085] Figure 2 Bi in Example 1 3+ Doped Ca5Ga 4.8 Al 1.2 O 14 : 0.006Bi 3+ , 0.06Sm 3+ ,0.06Tb 3+ Scanning electron microscope image of the mechanoluminescent material.
[0086] Figure 3 The left figure in the figure is the exploration of Bi in Example 1, Example 3 to Example 5 3+ The effect of concentration on the intensity of yellow photoluminescence; the right figure is the exploration of Bi in Example 2, Example 6 to Example 8 3+ The effect of concentration on the red photoluminescence intensity shows that when the doping amount is 0.006Bi 3+ The best mesoluminescence is shown when . This may be because when the doping concentration is low, the trap concentration is low and the mesoluminescence intensity of the material is low; when the doping concentration is too high, concentration quenching occurs and the mesoluminescence intensity of the material is low.
[0087] Figure 4 The middle left figure is a photoluminescence spectrum diagram and a physical picture of Example 1 and Example 2 under a 365-nanometer ultraviolet lamp. It can be seen from the figure that the material of the present invention can achieve photoluminescence from yellow to red; Figure 4 The middle right figure is the spectrum diagram and the actual picture of the mechanoluminescent nanostructures of Example 1 and Example 2. It can be seen from the figure that the material of the present invention can realize mechanoluminescence from yellow to red.
[0088] Figure 5 The two-color mechanoluminescent materials of Examples 1 and 2 are mechanoluminescent effects that last for 15 days without charging, indicating that the materials have very good stability.
[0089] Application Example 1
[0090] The mechanoluminescent material of Example 1, epoxy resin A glue (molding agent), and epoxy resin B glue (curing agent) are fully mixed in a mass ratio of 4: 3: 1 and put into a mold, and then heated at a constant temperature of 60° C. in an oven for 60 minutes to finally obtain a composite of mechanoluminescent material and epoxy resin (mechanoluminescent composite material), and then the mechanoluminescent composite material is used for product anti-counterfeiting.
[0091] The mechanoluminescent composite material of Application Example 1 can be prepared into any pattern or text as required. Figure 6This is a schematic diagram of the use of the mechanoluminescent composite material for commodity anti-counterfeiting in Application Example 1. A mechanoluminescent anti-counterfeiting coating is prepared on the surface of a wine bottle. When the anti-counterfeiting coating is removed, mechanoluminescence is generated due to the force applied to the material.
[0092] The Bi provided by the present invention 3+ Doped Ca5Ga 4.8 Al 1.2 O 14 : 0.006Bi 3+ , 0.06Sm 3+ or Ca5Ga 4.8 Al 1.2 O 14 : 0.006Bi 3+ , 0.06Sm 3+ , 0.06Tb 3+ The mechanoluminescent material is a mechanoluminescent material with high stability and excellent optical properties, with adjustable color from yellow to red. The present invention successfully prepared a color-adjustable mechanoluminescent material that does not require pre-irradiation, which is expected to be promoted and applied in the field of commodity anti-counterfeiting labels, and provides a new reference for the development of new intelligent anti-counterfeiting materials.
[0093] Although the above-mentioned embodiments have made a detailed description of the present invention, they are only some embodiments of the present invention, rather than all embodiments. People can also obtain other embodiments based on the embodiments of the present invention without creative work, and these embodiments all fall within the scope of protection of the present invention.
Claims
1. A mechanoluminescent material, characterized in that: The chemical formula is Ca5Ga 4.8 Al 1.2 O 14 :D, wherein D is Bi 3+ and Sm 3+ ; The Bi 3+ and Sm 3+ The molar ratio of substances is (0.002~0.008):(0.02~0.12).
2. A mechanoluminescent material, characterized in that: The chemical formula is Ca5Ga 4.8 Al 1.2 O 14 :D, wherein D is Bi 3+ 、Sm 3+ and Tb 3 + ; The Bi 3+ 、Sm 3+ and Tb 3+ The molar ratio of substances is (0.002~0.008):(0.02~0.12):(0.02~0.12).
3. The method for preparing the mechanoluminescent material according to claim 1, characterized in that: The following steps are involved: H3BO3, Al2O3, CaO, Ga2O3, Bi2O3 and Sm2O3 are mixed and calcined to obtain the mechanoluminescent material.
4. The preparation method according to claim 3, characterized in that: The calcination temperature is 1170-1270° C., and the heat preservation time is 3.5-5.5 hours.
5. The preparation method according to claim 3, characterized in that: The molar ratio of H3BO3, Al2O3, CaO, Ga2O3, Bi2O3 and Sm2O3 is (0.001~0.003):0.6:(4.5~5.5):2.4:(0.001~0.004):(0.01~0.06).
6. The method for preparing the mechanoluminescent material according to claim 2, characterized in that: The following steps are involved: H3BO3, Al2O3, CaO, Ga2O3, Bi2O3, Sm2O3 and Tb4O7 are mixed and calcined to obtain the mechanoluminescent material.
7. The preparation method according to claim 6, characterized in that: The molar ratio of H3BO3, Al2O3, CaO, Ga2O3, Bi2O3, Sm2O3 and Tb4O7 is (0.001~0.003):0.6:(4.5~5.5):2.4:(0.001~0.004):(0.01~0.06):(0.01~0.06).
8. Use of the mechanoluminescent material according to claim 1 or 2 or the mechanoluminescent material obtained by the preparation method according to any one of claims 3 to 7 in anti-counterfeiting labels.
9. A mechanoluminescent composite material, characterized in that: Including the following raw materials by mass: 3.5~4.5 parts of mechanoluminescent material, 2.5~3.5 parts of molding agent and 0.8~1.2 parts of curing agent; The mechanoluminescent material is the mechanoluminescent material according to claim 1 or 2 or the mechanoluminescent material obtained by the preparation method according to any one of claims 3 to 7.
Citation Information
Patent Citations
Mechanoluminescence composite material as well as preparation method and application thereof
CN111909689A
Three-mode dynamic color-changing anti-counterfeiting material and preparation method thereof
CN111925787A
Multicolor mechanoluminescence fluorescent powder and preparation method and anti-counterfeiting application thereof
CN117887458A